High Diversity and Functional Potential of Undescribed “Acidobacteriota” in Danish Wastewater Treatment Plants - Kristensen, Jannie Munk; Singleton, Caitlin; Clegg, Lee-Ann; Petriglieri, Francesca; Nielsen, Per Halkjaer (Frontiers in Microbiology, 2021)
Microbial communities in water resource recovery facilities encompass a large diversity of poorly characterized lineages that could have undescribed process-critical functions. Recently, it was shown that taxa belonging to “Acidobacteriota” are abundant in Danish full-scale activated sludge wastewater treatment plants (WWTP), and here we investigated their diversity, distribution, and functional potential. “Acidobacteriota” taxa were identified using a comprehensive full-length 16S rRNA gene reference dataset and amplicon sequencing surveys across 37 WWTPs. Members of this phylum were diverse, belonging to 14 families, 8 of which are completely uncharacterized and lack type strains. Several lineages were abundant, with relative abundances of up to 5% of the microbial community. Genome annotation and metabolic reconstruction of 50 high-quality “Acidobacteriota” metagenome-assembled genomes from 19 WWTPs showed high metabolic diversity and potential involvement in nitrogen and phosphorus removal and iron reduction. Fluorescence in situ hybridization (FISH) using newly-designed probes revealed cells with diverse morphologies, predominantly located inside activated sludge flocs. FISH in combination with Raman microspectroscopy revealed ecophysiological traits in probe-defined cells from the families Holophagaceae, Thermoanaerobaculaceae, Vicinamibacteraceae, and families with the placeholder name of midas_f_502, midas_f_973, and midas_f_1548. Members of these lineages had the potential to be polyphosphate-accumulating organisms as intracellular storage was observed for the key compounds polyphosphate and glycogen.